Media Sosial, Orientasi Pasar, dan Nilai Pelanggan sebagai Determinan Kinerja Pemasaran UMKM di Wilayah Tutur, Pasuruan - Alaika Asrori Almagrobi; Nuraeni Nuraeni; Miftahul Huda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of social media utilization, market orientation, and customer value on marketing performance among Micro, Small, and Medium Enterprises (MSMEs) in Tutur District, Pasuruan Regency. A quantitative approach was applied through a survey of 30 MSME actors who utilize social media platforms such as Instagram and Facebook. Multiple linear regression analysis was employed. The results indicate that all three independent variables have a positive and significant influence, both partially and simultaneously, on marketing performance. This research contributes theoretically to the digital marketing literature and provides practical implications for MSMEs in optimizing their social media strategies.